Controlling radiofrequency‐induced currents in guidewires using parallel transmit. Issue 6 (17th December 2014) - Etezadi‐Amoli, Maryam; Stang, Pascal; Kerr, Adam; Pauly, John; Scott, Greig
Abstract : Purpose: Elongated conductors, such as pacemaker leads, neurostimulator leads, and conductive guidewires used for interventional procedures can couple to the MRI radiofrequency (RF) transmit field, potentially causing dangerous tissue heating. The purpose of this study was to demonstrate the feasibility of using parallel transmit to control induced RF currents in elongated conductors, thereby reducing the RF heating hazard. Methods: Phantom experiments were performed on a four‐channel parallel transmit system at 1.5T. Parallel transmit "null mode" excitations that induce minimal wire current were designed using coupling measurements derived from axial B1 + maps. The resulting current reduction performance was evaluated with B1 + maps, current sensor measurements, and fluoroptic temperature probe measurements. Results: Null mode excitations reduced the maximum coupling mode current by factors ranging from 2 to 80. For the straight wire experiment, a current null imposed at a single wire location was sufficient to reduce tip heating below detectable levels. For longer insertion lengths and a curved geometry, imposing current nulls at two wire locations resulted in more distributed current reduction along the wire length. Conclusion: Parallel transmit can be used to create excitations that induce minimal RF current in elongated conductors, thereby decreasing the RF heating risk, while still allowing visualization of the surrounding volume. Magn Reson Med 74:1790–1802, 2015. © 2014 Wiley Periodicals, Inc.